Flipped Learning Instruction to Enhance University Students’ Higher Order Thinking Skills - Suprapti, Suprapti; Nugroho, Arif; Pembangunan, Heldy Ramadan Putra (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to shed some light on the significant impact of content videos in flipped learning classroom on students’ higher order thinking skills. The secondary aim of this study is to portray students’ perception toward the practice of flipped learning in assisting their higher order thinking skill development. A total of 36 elementary teacher education students at IAIN Surakarta are involved as participants in this pre-experimental study. Drawing on pre-test, post-test, and focus group discussion, the results of paired sample t-test show a significant difference on the students’ score of pre-test and post-test, meaning that flipped learning with content videos is effective to enhance the students’ higher order thinking skills. Furthermore, the focus group discussion reveals that the students positively perceive the practice of flipped learning instruction to enhance their higher order thinking skills. These results contribute to providing fruitful insights for teachers and school administrators as a teaching model to enhance students’ higher order thinking skills.